Bioinks adapted for in situ bioprinting scenarios of defect sites: a review. Issue 11 (3rd March 2023) - Li, Ruojing; Zhao, Yeying; Zheng, Zhiqiang; Liu, Yangyang; Song, Shurui; Song, Lei; Ren, Jianan; Dong, Jing; Wang, Peige
Abstract : Design points and applicable scenarios for bioinks in in situ 3D bioprinting. Abstract : In situ bioprinting provides a reliable solution to the problem of in vitro tissue culture and vascularization by printing tissue directly at the site of injury or defect and maturing the printed tissue using the natural cell microenvironment in vivo . As an emerging field, in situ bioprinting is based on computer-assisted scanning results of the defect site and is able to print cells directly at this site with biomaterials, bioactive factors, and other materials without the need to transfer prefabricated grafts as with traditional in vitro 3D bioprinting methods, and the resulting grafts can accurately adapt to the target defect site. However, one of the important reasons hindering the development of in situ bioprinting is the absence of suitable bioinks. In this review, we will summarize bioinks developed in recent years that can adapt to in situ printing scenarios at the defect site, considering three aspects: the in situ design strategy of bioink, the selection of commonly used biomaterials, and the application of bioprinting to different treatment scenarios.